Recombinant canarypox virus expressing the VP2 protein of infectious bursal disease virus induces protection in vaccinated SPF chickens - Zanetti, Flavia Adriana; Cardona, Romina; Federico, Carlos Rodolfo; Chimeno Zoth, Silvina Andrea; Calamante, Gabriela (2017)
To study the in vivo distribution of the CNPV viral vector, we conducted two trials. In the first trial, six 11- day-old SPF chickens were intramuscularly vaccinated in one leg with CN048-VP2 (106 plaque-forming units (PFU) mixed with 0.5% v/v Indian ink). Three birds were sacrificed at 1 and 3 days after vaccination, and muscle at the immunization site (identified by Indian ink), muscle from the non-injected leg, BF, and spleen were removed, weighed, and homogenized in phosphate buffer (50% w/v). Total DNA was extracted from organs using a QIAamp® DNA Mini Kit (QIAGEN, USA) and used as the template for PCR amplification of CNPV241 (primers P39F: 5′-AATAACACGACACAGCCGCAAG-3′, P39R: 5′-CAATTAATTAGATCGTGGTGGA-3′) or the glyceraldehyde-3-phosphate dehydrogenase (gapdh) gene (primers GAPDH Fw: 5′-AGAACATCATCCCAGCGTCC-3′, GAPDH Rv: 5′-CGGCAGGTCAGGTCAACA-3′).